FDI A Challenge or an Opportunity: Exploring the Impact of FDI on India's Path to Superpower Status (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the course of recent decades, FDI's awesome and phenomenal development inside the worldwide financial scene has made it a basic piece of both created and building up countries' advancement system. It goes about as a significant impetus in a nation's advancement through innovation overhauling, administrative aptitudes and abilities across various parts. Expanding buying power, developing commercialization, and expansion of brands have prompted retail modernization in India. The accompanying article tends to Indian FDI or Foreign Direct Investment. Numerous individuals are for FDI and many individuals are against it. However, in the wake of taking all the contentions in favor and against FDI into thought, one can securely infer that it has a bigger number of benefits than the bad marks appended to it, and if India needs to advance further and turn into a super force, the Indian government needs to pull out all the stops.